Platform Collusion in Two-Sided Markets - Isabel Ruhmer (Verein für Socialpolitik, 2010)
This papers analyses price collusion between platforms in a two-sided market model based on Armstrong (2006). In particular, it addresses Evans and Schmalensee's hypothesis of collusion being harder to sustain because of feedback effects and stronger requirements concerning agreements and monitoring. Results imply that growing indirect network externalities have two opposing effects on the sustainabilty of a cartel. First, collusive profits increase while stage game Nash profits fall making collusion more desirable. Second, however, the incentive to deviate increases as demand reactions become stronger. In total, the latter effect dominates and collusion becomes harder to sustain as indirect network externalities increase.
Keywords: L41; L12; L40; 330